Evaluation of Processing Tomato Pomace after Composting on Soil Properties, Yield, and Quality of Processing Tomato in Greece - Ioanna Kakabouki; Antigolena Folina; Aspasia Efthimiadou; Stella Karydogianni; Charikleia Zisi; Varvara Kouneli; Nikolaos C. Kapsalis; Nikolaos Katsenios; Ilias Travlos (Agronomy, 2021)
While processing tomato cultivation (Solanum lycopersicum L.) is considered one of the most important industrial crops in Greece, a waste known as tomato pomace is growing significantly high. Notably, the tomato pomace presents enormous opportunities for the creations of organic fertilizers. The aim of this study was to investigate the use of tomato pomace as a fertilizer in the same crop. A field experiment was established at the Agricultural University of Athens during 2018 and 2019 in a randomized complete design with five treatments (control, inorganic NPK (NPK), Tomato pomace and Biocycle Humus Soil (Tp and BHS), Tomato pomace and Farmyard manure (Tp and FYM), and Tomato pomace and Compost (Tp and CM). Physical soil properties such as soil porosity and penetration resistance were improved by the application of organic blends. Additionally, soil nitrogen content ranged from 0.10% (control and NPK) to 0.13% (Tp and FYM). A significant increase of yield was noticed under organic fertilization where the highest yield of 8.00 tn ha−1 was recorded in Tp and BHS (2018). Lycopene content was significantly affected by fertilization and its highest values were 87.25 (Tp and BHS; 2018), and 88.82 mg kg−1 fresh (Tp and FYM; 2019). Regarding fruit firmness, the three organic blends did not have statistically significant difference. In addition, the Total Soluble Solids (TSS) was significantly affected by the fertilization and the maximum value was 4.80 ◦Brix (Tp and CM; 2018). In brief, tomato pomace blended with organic fertilizers was yielded considerable since it improved soil quality and increased yield.